Designing Adjuvant Formulations to Promote Immunogenicity and Protective Efficacy of Leptospira Immunoglobulin-Like Protein A Subunit Vaccine - Techawiwattanaboon, Teerasit; Courant, Thomas; Brunner, Livia; Sathean-anan-kun, Suwitra; Krangvichian, Pratomporn; Iadsee, Nutta; Nakornpakdee, Yaowarin; Sangjun, Noppadon; Komanee, Pat; Collin, Nicolas; Ruxrungtham, Kiat; Patarakul, Kanitha (Frontiers in Cellular and Infection Microbiology, 2022)
The leptospirosis burden of humans especially in high-risk occupational group and livestock leads to public health and economic problems. Leptospirosis subunit vaccines have been under development and required further improvement to provide complete protection. Adjuvants can be used to enhance the amplitude, quality, and durability of immune responses. Previously, we demonstrated that LMQ adjuvant (neutral liposomes containing monophosphoryl lipid A (MPL) and Quillaja saponaria derived QS21 saponin) promoted protective efficacy of LigAc vaccine against Leptospira challenge. To promote immunogenicity and protective efficacy of the subunit vaccines, three alternative adjuvants based on neutral liposomes or squalene-in-water emulsion were evaluated in this study. LQ and LQuil adjuvants combined the neutral liposomes with the QS21 saponin or Quillaja saponaria derived QuilA® saponin, respectively. SQuil adjuvant combined a squalene-in-water emulsion with the QuilA® saponin. The immunogenicity and protective efficacy of LigAc formulated with the candidate adjuvants was conducted in golden Syrian hamsters. Hamsters were vaccinated three times at 2-week interval followed by homologous challenge of L. interrogans serovar Pomona. The results showed that LigAc combined with LQ, LQuil, or SQuil adjuvants conferred substantial antibody responses and protective efficacy (survival rate, pathological change, and Leptospira renal colonization) comparable to LMQ adjuvant. This study highlights the potential of saponin-containing adjuvants LMQ, LQ, LQuil and SQuil for both human and animal leptospirosis vaccines.